Semiotics of Protest Movements. The No Global Model - Cosenza, Giovanna (E|C, 2022)
Studying social movements (or protest movements) is interesting not only for contentious politics, but for all disciplines dealing with political communication and for all kinds of marketing -commercial, public, social, even personal. The paper proposes a semiotic analysis of the no-global movement which is considered as a model since it shares some characteristic traits with most of those that have succeeded it. Furthermore, its failure is a warning to all subjects that build their identity on the denial of something or someone.